Persepsi dan Harapan Wisatawan berdasarkan Kualitas Layanan Wisata Panjat Tebing dengan Metode SERVQUAL - Meliza; Alimuddin; Sonya Nelson; Ilham; Ridho Bahtra (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study analyzed tourists’ perceptions of rock-climbing tourism service quality in Harau Valley using the five SERVQUAL dimensions and identified expectations for service improvement. A descriptive quantitative design with supporting qualitative data was employed. Thirty tourists were selected purposively; 60% had climbed at least five times. Data were collected through observation, a 60-item questionnaire, semi-structured interviews, and documentation. All items were valid, and Cronbach’s alpha coefficients across the five dimensions ranged from 0.788 to 0.910. The analysis used descriptive statistics, mean scores, respondent achievement percentages, and interview interpretation. Empathy reached 84.23%, Reliability 82.50%, and Responsiveness 75.32%, all in the good category, whereas Tangibles and Assurance each reached 51.41% and were categorized as poor. Tourists emphasized improvements in facilities, access, route information, equipment completeness, safety procedures, guide competence, and emergency preparedness. The findings indicate that service strengths lie in interpersonal interaction, while the main priorities are physical evidence and safety assurance. Management should also account for visitors’ experience levels, weather conditions, risk perceptions, and environmental carrying capacity so that increased visitation remains safe and sustainable.